1989
DOI: 10.1111/j.1432-1033.1989.tb14514.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physicochemical requirements of endotoxins for the activation of arachidonic acid metabolism in mouse peritoneal macrophages in vitro

Abstract: Lipopolysaccharides of different wild-type and mutant gram-negative bacteria, as well as synthetic and bacterial free lipid A, were studied for their ability to activate arachidonic acid metabolism in mouse peritoneal macrophages in vitro. It was found that lipopolysaccharides of deep-rough mutants of Saln~onellu minnesotu and Escherirhia coli (Re to Rc chemotypes) stimulated macrophages to release significant amounts of leukotriene C4 (LTC,) and prostaglandin E2 (PGE,). Lipopolysaccharides of wild-type strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…The above data differ from those of Brown and colleagues (34) who determined that normal human AM release only cyclooxygenase products after challenge with endotoxin. Luderitz and co-workers (35) have established that different LPS vary in their capacity to effect leukotriene release from mouse peritoneal macrophages. Thus, the difference between the findings of Brown and co-workers and those of our study possibly may be explained in part, by the use of a different serotype of LPS and/or by other undefined conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The above data differ from those of Brown and colleagues (34) who determined that normal human AM release only cyclooxygenase products after challenge with endotoxin. Luderitz and co-workers (35) have established that different LPS vary in their capacity to effect leukotriene release from mouse peritoneal macrophages. Thus, the difference between the findings of Brown and co-workers and those of our study possibly may be explained in part, by the use of a different serotype of LPS and/or by other undefined conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We have described in an earlier paper a correlation between the /3 ++ ci phase-transition temperatures of wild-type and various rough mutant lipopolysaccharide and of free lipid A from S. minnesota with their ability to induce the release of leukotriene C4 from mouse peritoneal macrophages [25]. We showed that this ability is highest for lipopolysaccharide Re (lowest t,) and lowest for free lipid A (highest t,) and decreases with increasing completeness of the sugar moiety (tc increasing with respect to Re lipopolysaccharide).…”
Section: Correlation Of Biological Effectsmentioning
confidence: 98%
“…In view of the known significance of the polysaccharide portion for serological specificity [ l l ] and of the inner core region for the modulation of lipid A toxicity [12,131, the activation of complement [14], and the binding of 28-kDa serum factor [15] it seemed rewarding to analyze its primary chemical structure.…”
Section: P-d-galpmentioning
confidence: 99%